Integration of the insurance industry in the European Community and its implications for the Turkish insurance market - Kocaman, Vildan (My University, 1993)
unknown
Keywords: A.E.T.-SİGORTACILIK; Ekonomi; SİGORTACILIK-A.E.T; SİGORTACILIK-TÜRKİYE